2000
DOI: 10.1097/00007632-200005150-00007
|View full text |Cite
|
Sign up to set email alerts
|

The Cervical Facet Capsule and Its Role in Whiplash Injury

Abstract: Pretorque of the head and neck increases facet capsular strains, supporting its role in the whiplash mechanism. Although the facet capsule does not appear to be at risk for gross injury during normal bending motions, a small portion of the population may be at risk for subcatastrophic injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
142
1
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 186 publications
(157 citation statements)
references
References 28 publications
11
142
1
3
Order By: Relevance
“…Mykelbust et al (1988) reported failure forces of 112±30 N and 72±18 N for 20 tensile loading of isolated C3/C4 and C5/C6 ligaments, respectively. Likewise, 21 Winkelstein et al (2000) reported ligament failure at similar forces of 94.3±44.4 N and 22 82.5±33.0 N for these same joints. In that study, maximum ligament distraction at failure 23 was 5.10±0.73 mm and 6.40±0.66 mm, respectively, producing maximum principal 24 strains of 103.6±80.9% in the facet capsule (Winkelstein et al 2000).…”
Section: Introductionmentioning
confidence: 68%
See 4 more Smart Citations
“…Mykelbust et al (1988) reported failure forces of 112±30 N and 72±18 N for 20 tensile loading of isolated C3/C4 and C5/C6 ligaments, respectively. Likewise, 21 Winkelstein et al (2000) reported ligament failure at similar forces of 94.3±44.4 N and 22 82.5±33.0 N for these same joints. In that study, maximum ligament distraction at failure 23 was 5.10±0.73 mm and 6.40±0.66 mm, respectively, producing maximum principal 24 strains of 103.6±80.9% in the facet capsule (Winkelstein et al 2000).…”
Section: Introductionmentioning
confidence: 68%
“…Likewise, 21 Winkelstein et al (2000) reported ligament failure at similar forces of 94.3±44.4 N and 22 82.5±33.0 N for these same joints. In that study, maximum ligament distraction at failure 23 was 5.10±0.73 mm and 6.40±0.66 mm, respectively, producing maximum principal 24 strains of 103.6±80.9% in the facet capsule (Winkelstein et al 2000). In tensile failure 25 tests of lower cervical spine specimens (C5-T1), Yoganandan et al (2000) reported 26 stresses of 7.4±1.3 MPa and strains of 116.0±19.6%, with corresponding stiffness and 27 energy to failure of 36.9±6.06 N/mm and 1.5±0.4 Nm, respectively.…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations